Afinação vocal: vivência musical e processamento auditivo temporal em cantores populares - Marques, Juliana Fernandes (2019)
Introduction: vocal tuning can be defined as the proper reproduction of isolated notes or musical words that can vary in frequency and follow different evaluation criteria according to the cultural and historical context in which the singer is inserted. The literature has showed that the vocal tuning can be evaluated by multiple factors like the exposition to music along somebody’s life and a refined temporal hearing processing. Thus, it can be assumed that tuned and out of tune singers show different life experiences and performances in the evaluation of the hearing processing. Objective: compare the influence of the musical experience ante the performance in the temporal hearing processing in tuned and out of tune popular singers. Method: the sample was composed by 14 professional popular singers who were divided in two groups by two vocal screening instruments: one group with seven tuned singers and the other group with seven out of tune singers. All subjects answered a sample characterization sheet and a questionnaire of musical experience, the second one approached issue related to the singer's musical experience. The evaluation of the temporal hearing processing was performed by the following tests: Frequency Pattern Test, Duration Pattern Test and Gap in Noise. Results: tuned singers stated that they have been exposed to a musical environment since their childhood, studied music for a long time, had secondary jobs more related to music and showed a better performance in the temporal hearing processing tests than out of tune singer group. Conclusion: tuned singers have showed a bigger musical life experience and better temporal patterns than out of tune singers